An Analysis of Students’ Difficulties in Listening Comprehension at SMAN 1 Muara teweh - Fatonah, Yulia; Rahmadani, Nur; Azmi, Aulia; Azmi, Aulia (Journal of English Teaching, Literature, and Applied Linguistics, 2024)
Listening is the first skill of English that should learned by students. This is because before students can respond to their teachers, they must listen first to get information and concepts. Moreover, there are still many students who have difficulties in listening comprehension. This study to find out students’ difficulties and factors that cause students’ difficulties in listening comprehension of Eleventh-grade students in SMAN 1 Muara Teweh. This study used quantitative descriptive research design and sampling technique using cluster random sampling. Data collection instrument used questionnaire. From the data analysis, as many as 49% of students have difficulty related to listening material, 52.8% of students have difficulty related to the listener, and 82% of students have difficulty related to physical setting. Besides, the factors that cause students’ difficulties in listening comprehension were depend on others, and shame to ask the teacher about the material. Based on the results of the research, it can be concluded that most students have some difficulties in listening comprehension, which has constrained their ability to improve their listening skills. Keywords: Factors; Listening Comprehension; Students’ Difficulties